2012
DOI: 10.2174/138161212803307572
|View full text |Cite
|
Sign up to set email alerts
|

The use of Human Allogenic Graft (HBA) for Maxillary Bone Regeneration: Review of Literature and Case Reports

Abstract: The use of graft materials is developed from the strong demand to support the complete bone regeneration of the empty socket and to increase the bone volume in treating the atrophies of sites already consolidated and with adverse alveolar bone conditions. A number of graft materials with different origin and mechanism of bone regeneration are available. Autologous graft materials, coming from the same patient, are defined as the gold-standard. The need of a second surgical site and the risk of morbidity and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Different bone grafting materials can be used: intraoral or extraoral autologous bone, homologous grafts, heterologous grafts, and alloplastic grafts that can be used alone or in combination with others. [9][10][11] Among them, autologous bone has long been considered the ideal grafting material in bone reconstructive surgery; however, it presents some disadvantages, including morbidity, availability, and unpredictable graft resorption. 12,13 A good alternative for the use of autologous bone is the homologous bone allograft, which is also available in different types: freeze-dried bone allograft (FDBA), decalcified FDBA, fresh bone, and fresh frozen bone (FFB).…”
Section: Introductionmentioning
confidence: 99%
“…Different bone grafting materials can be used: intraoral or extraoral autologous bone, homologous grafts, heterologous grafts, and alloplastic grafts that can be used alone or in combination with others. [9][10][11] Among them, autologous bone has long been considered the ideal grafting material in bone reconstructive surgery; however, it presents some disadvantages, including morbidity, availability, and unpredictable graft resorption. 12,13 A good alternative for the use of autologous bone is the homologous bone allograft, which is also available in different types: freeze-dried bone allograft (FDBA), decalcified FDBA, fresh bone, and fresh frozen bone (FFB).…”
Section: Introductionmentioning
confidence: 99%
“…Mineralized human bone allograft was used to enhance atrophic maxillary floors in sinuses of various sizes, and the results demonstrated that this material promoted adequate bone growth [61]. Histologic analysis of mineralized freeze-dried bone allografts for sinus augmentation indicated a mean of 29.1% newly created bone, with graft particles largely in close contact with newly formed bone, primarily with mature bone characteristics such as many osteocytes [62]. Other reports found that the majority of the specimens had newly produced bone and that the interface areas between new and old bone were not apparent.…”
Section: Allograftmentioning
confidence: 99%
“…To date, various graft materials have been successfully used for SFE solely or in combination with each other [17], such as autograft [18][19][20][21] (intraoral: chin, retromolar region, mandibular ramus, maxillary tuberosity [22,23]; extraoral: iliac crest, fibula, tibia [24][25][26]), allograft [27][28][29] (fresh, frozen, freeze-dried bone [30,31]), xenograft [32][33][34][35][36] (deproteinized bovine bone [37][38][39]), and phytogenic material [39][40][41] (Gusuibu, coral-based bone substitutes, and marine algae).…”
Section: Introductionmentioning
confidence: 99%